Monodisperse Highly Ordered and Polydisperse Biobased Solid Foams - Andrieux, Sébastien; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses the synthesis of chitosan-based solid foams using foam templating. Solid foams with pore sizes between a few micrometres and a few millimetres are widely used in a range of established and emerging applications, including filtration, catalysis, sound and thermal insulation, human protection, and tissue engineering. They are lightweight with large surface-to-volume ratios, and have excellent mechanical, acoustic, and thermal properties. However, most foaming processes are extremely complex, and there remains a lack of sound scientific understanding of-and therefore control over-the parameters that determine the properties of the material. One route towards tailor-made solid foams is liquid foam templating, where the liquid foam is generated first (with the desired structure) before being solidified into a solid foam with the desired structure. This book describes how liquid foam templating can be used to synthesise monodisperse solid foams as well as solid foams with a tuneable polydispersity.
Introduction -- Theoretical Background -- Preliminary Work: From Liquid to Solid Foams -- Monodispers and Polydisperse Chitosan Foams via Microfluidics,. Monodisperse Highly Ordered Nanocomposite Foams -- General Conclusion and Outlook -- Experimental.
Keywords: Polymers; Soft condensed matter; Biomaterials; Materials; Polymers; Soft and Granular Matter; Biomaterials; Materials Engineering